Dinâmica do carbono orgânico total no rio Cuiabá – Mato Grosso - Abreu, Caroline Antunes Agostinho de (2016)
Studies on the seasonal dynamics of carbon in tropical aquatic ecosystems are important for understanding ecological relationships and changes related to man-made impacts. In the Upper Paraguay River Basin – UPRB there is little information on how this dynamic occurs in the rivers of Pantanal Wetland, such as the Cuiabá River, in Mato Grosso State. The objective of this research was to quantify the concentrations and the loads of total organic carbon (TOC) related to the hydrological cycle. The water samples were collected monthly between August/2012 and December/2013 and later, between September/2014 and April/2015, in four sampling points located in the municipalities of Rosário Oeste (RO, upstream), Várzea Grande (Passagem do Conceição - PC), Santo Antônio do Leverger (SA), and Poconé (Porto Cercado – CER, downstream). In addition, a single collection was carried out in January/2015, in the Pantanal Mato-grossense National Park region (PARNA), where two points were sampled on the Cuiabá River (upstream - PJ and downstream - SP of a marginal lake - Baía do Burro) and other two in the marginal lakes of the flood area, adjacent to the river main channel, Baía do Burro (BB) and Baía do Morro (BM). Composite samples (margins and center) were collected at 60 cm depth, preserved with H3PO4 at pH ≤ 2.0 and kept under refrigeration followed by freezing in the laboratory. The basic parameters pH, temperature, electrical conductivity and dissolved oxygen were measured in situ, using Hanna - Model HI 9828 portable multiparametric equipment, properly calibrated. For the quantification of the alkalinity samples were collected in the central part of the river, being analyzed by titration with HCl 0,0501 mol L-1 in an automatic titrator. The values of pH, temperature and alkalinity were used for the indirect calculation of concentrations of free carbon dioxide (CO2L). The TOC analysis was performed in AURORA 1030W TOC, with automatic sampler, in triplicate, using ultra-pure water obtained from GEHAKA Purifier. For the calculation of the total organic carbon load for the years 2014 to 2015, the flow data were measured at the time of sampling at each point in m3 s -1 (Qy), and for the years 2012 to 2013 were used data from ANA Data Basis - Hidroweb, multiplied by the corresponding TOC levels in mg L-1 (Cs), and determining the load in t-day (Qss) by the following expression: Qss = 0.0864. Qy. Cs. The results of TOC concentration ranged from 1.11 mg L-1 to 6.66 mg L -1 , and the highest values were observed during the flood phase. The same pattern was observed for the load results, with 670.1 t day-1 in SA, downstream of the Cuiabá-Várzea Grande metropolitan region, and 422.0 t day-1 at the upstream point - RO. The TOC datasets presented a normal distribution, allowing the application of analysis of variance - ANOVA to compare the observed averages along the Cuiabá River with the hydrological phases, drought and flood. The concentration data by hydrological period did not show statistically significant differences for both drought and flood, but for loads the results were statistically different in the dry season. The t-Test was also used to compare the concentration and load averages between the hydrological periods for each sampling point, at where RO and PC showing significant differences between the hydrological periods. The highest results were found in the flood season, both concentration: 3.17 mg L-1 - RO; 3.58 mg L-1 - PC; 4.01 mg L-1 - SA; 4.01 mg L-1 - CER; As well as the load: 149.96 t day-1 - RO; 216.46 t dia-1 - PC; 341.96 t dia-1 - SA; 172,28 t day-1 - CER, as a function of the increasing in runoff and discharges. The data obtained in the National Park (PARNA) were illustrative of this high flood stretch of the Pantanal of the Cuiabá River. The values observed in this lower section were higher than in the high and medium sections of the river. PJ, SP and BM presented, respectively, 7.76 mg L- 1 ; 7.01 mg L-1 , and 8.53 mg L-1 . The marginal lake BB, a highly heterotrophic environment, presented the highest value determined in this study, with 19.84 mg L-1 . In both SA and CE placed, respectively, at transition plateau/floodplain area and at floodplain itself, as in the lower section of the Cuiabá River, the phenomenon of “decoada” can influence the TOC contents because of the decomposition of submerged organic matter in the beginning of the flood phase. The higher concentrations of TOC in these points demonstrate that this variable is another indicative of the phenomenon. In an unparalleled study, we observed how much hydrodynamics influences the carbon (TOC) dynamics, a nutrient little studied in the UPRB, thus allowing us to estimate the load contributions of the Cuiabá River to the Pantanal Wetland.